2020
DOI: 10.1021/acs.inorgchem.9b02994
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Magnetic Anisotropy and Single-Molecule Magnet Behavior in Chromium(II)-Based Extended Metal Atom Chains

Abstract: S2 1. Synthesis General. Unless otherwise noted, reagents and solvents were of commercial origin and used without further purification. Naphthalene was resublimed and NaSCN was recrystallized from acetone before use. Dichloromethane and diethyl ether for the synthesis of 1a•Et2O were purified using an Inert Technologies solvent purification system. For the synthesis of 2a4CHCl32Et2O and 2b anhydrous dichloromethane (Sigma-Aldrich) was directly used, while chloroform was washed with water, stirred over CaCl2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 93 publications
7
37
0
Order By: Relevance
“…Meanwhile, the Cr even –Cr odd bonds are notably elongated by 0.194–0.318 Å, which is about 65–106 times larger than the above average reduction (0.003 Å), and their Wiberg bond indexes decreased from 0.606–0.706 to 0.185–0.305 (Figures S1 and S2). The bond lengths (2.519–2.542 Å in Table S4) are in agreement with the conclusion reported by Cornia et al that there can only be a very weak interaction ( d CrCr > 2.5 Å) . It was also observed that the configuration (Table S4) in 2.057 V nm –1 was similar to asymmetric Cr 7 (μ 7 -pzpz) 4 Cl 2 with pyrazine-modified oligo-α-pyridylamido ligands, as reported by Peng et al These significant changes suggest that the Cr even –Cr odd bonds experience weaker interactions and the Cr odd –Cr even multiple bonds are formed, which results in the switching from an on state to an off state .…”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Meanwhile, the Cr even –Cr odd bonds are notably elongated by 0.194–0.318 Å, which is about 65–106 times larger than the above average reduction (0.003 Å), and their Wiberg bond indexes decreased from 0.606–0.706 to 0.185–0.305 (Figures S1 and S2). The bond lengths (2.519–2.542 Å in Table S4) are in agreement with the conclusion reported by Cornia et al that there can only be a very weak interaction ( d CrCr > 2.5 Å) . It was also observed that the configuration (Table S4) in 2.057 V nm –1 was similar to asymmetric Cr 7 (μ 7 -pzpz) 4 Cl 2 with pyrazine-modified oligo-α-pyridylamido ligands, as reported by Peng et al These significant changes suggest that the Cr even –Cr odd bonds experience weaker interactions and the Cr odd –Cr even multiple bonds are formed, which results in the switching from an on state to an off state .…”
Section: Results and Discussionsupporting
confidence: 89%
“…Since the first report on the synthesis and structural characterization of [Cu 3 (dpa) 4 Cl 2 ] was published in 1990, a series of studies have been reported by Peng’s group, Berry’s group, , and Cornia’s group , to develop the structurally similar compounds and to study their molecular structures and physicochemical properties such as magnetic properties, electrical conductivity, and electrochemical properties. Cotton et al found that [Cr 3 (dpa) 4 Cl 2 ] exhibits an asymmetric configuration in benzene and toluene solvents, but in a more polar tetrahydrofuran solvent, it has a symmetric configuration with equal Cr–Cr bonds.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the linker effectively separates the magnetic subunits and no SCM behavior would be expected, only SMM. [73][74][75][76] The observed behavior and anisotropic values are similar to other published mononuclear Co(II) complexes in pseudo-octahedral geometry and also in other Co(II) CPs. [77][78][79][80][81][82] Dynamic susceptibility measurements were performed to study the possibility of slow relaxation of the magnetization.…”
Section: Magnetic Propertiessupporting
confidence: 88%
“…[ 29 , 30 , 31 ] The magnetic exchange interactions in the majority of these dimers is antiferromagnetic in nature. [ 32 , 33 ] Only few ferromagnetically coupled chromium(III) complexes have been reported. [ 34 , 35 , 36 ] Recently, a method for the targeted construction of ferromagnetically coupled chromium(III) complexes was reported.…”
Section: Introductionmentioning
confidence: 99%